Effects of thermal radiation on electrical MHD flow of nanofluid over stretching sheet - Daniel, Yahaya Shagaiya; Ismail, Zuhaila; Aziz, Zainal Abdul; Salah, Faisal (International Journal of Engineering and Technology, 2018)
The purpose of this investigation focuses on combined effects of thermal radiation, viscous dissipation and chemical reaction on unsteady magnetohydrodynamic (MHD) natural convection flow and heat transfer of nanofluid over a permeable stretching sheet with electric field effects. The governing equations are partial differential equations, converted to a couple of ordinary differential equations and then solved using implicit finite difference scheme. The electrical conducting nanofluid volume nanoparticle fraction on the boundary is passively rather than actively controlled. The effects of the emerging parameters on the electrical conducting nanofluid velocity, temperature, and nanoparticles concentration volume fraction with skin friction characteristics are examined with the aids of graphs and tabular form and then discussed extensively. Electric field enhances the nanofluid velocity which resolved the sticky effects caused by the magnetic field which suppressed the profiles. Radiative heat transfer and viscous dissipation are sensitive to an increase in the fluid temperature and thicker thermal boundary layer thickness. The nanoparticles concentration enhance with generative chemical reaction while opposite trend occurs for destructive chemical reaction. Comparison with published results is examined and presented which are found to be in good agreement.Â